Severe Acute Generalized Exanthematous Pustulosis Successfully Treated by Spesolimab - Giuseppe Russo; Shireen Dumont; Sébastien Menzinger; Damien Pastor; Laurence Toutous Trellu; Gürkan Kaya; Emmanuel Laffitte (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)